2003
DOI: 10.1002/cbf.1075
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin‐associated sphingomyelin: metabolism in relation to cell function

Abstract: After the first histochemical demonstration by Chayen and Gahan of the presence of phospholipids and especially of sphingomyelin in chromatin, this became the object of long debate and of contradictory results. The general conclusion was that the presence of phospholipids may due to contamination during the isolation of chromatin. More recently the existence of a phospholipid chromatin fraction was confirmed by demonstrating that isolated hepatocyte nuclei, labelled by saturated and unsaturated radioiodination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Many studies indicate that SM synthase is located mainly in the cis -medial Golgi (19)(20)(21) and plasma membranes (22)(23)(24). In addition, SMS activity has been found in chromatin, and chromatin-associated SMS modifies SM content (25)(26)(27). Despite the biological importance of SMS, understanding of the molecular mechanisms of its regulation and its relationship with plasma SM levels is limited by the fact that no successful purification of this protein has been achieved.…”
mentioning
confidence: 99%
“…Many studies indicate that SM synthase is located mainly in the cis -medial Golgi (19)(20)(21) and plasma membranes (22)(23)(24). In addition, SMS activity has been found in chromatin, and chromatin-associated SMS modifies SM content (25)(26)(27). Despite the biological importance of SMS, understanding of the molecular mechanisms of its regulation and its relationship with plasma SM levels is limited by the fact that no successful purification of this protein has been achieved.…”
mentioning
confidence: 99%
“…As consequence of nuclear SMase activity, a peak of nuclear ceramide was observed 2 h after deprivation followed by a decrease in SM content. In fact the activation of SMase was accompanied by an inhibition of SM-synthase suggesting a reciprocal control between the two enzymes as previously observed in hepatocyte nuclei (Albi and Viola Magni, 2003a). An increase of SMase in the homogenate was observed only 8 h after deprivation, when the number of HN9.10.e cells in the S phase begins to decrease with a corresponding increase of the cells in G 1 .…”
Section: Discussionmentioning
confidence: 63%
“…While this data brings into question the fidelity of the 13 C labeling procedure it is interesting to note that a number of studies have indicated that a multitude of phospholipids may be metabolized and associated with nuclear assemblages [68][69][70] .…”
Section: Isotopic Label Incorporation and Heterogeneitymentioning
confidence: 99%
“…In addition, evidence indicates that a variety of phospholipids may act as lipid mediators during nuclear processes such as DNA transcription, splicing and repair 69,70 . The cellular metabolism of lipids, then, may have resulted in the distribution of the 13 C label to an array of viral components during inter-cellular virion assembly.…”
Section: Isotopic Label Incorporation and Heterogeneitymentioning
confidence: 99%